PENGETAHUAN DAN SIKAP MAHASISWA DALAM PENCEGAHAN COVID-19 - Fauzan Alfikrie; Ali Akbar; Yunita Dwi Anggreini (Akademi Keperawatan Yarsi Samarinda, 2021)
The role of nursing students is an important part of efforts to tackle the Covid-19 pandemic. Students can become rolemodel in society by showing behavior in preventing Covid-19. Good knowledge and a positive attitude in preventing Covid-19 can be an effort to break the transmission of Covid-19. The purpose of this study was to determine the relationship between knowledge, attitudes and Covid-19 prevention behavior in nursing students. The design used in this study is an analytic observational study using the chi-square analysis. A total of 40 respondents who participated in this study were female (67.5%) and male (32.5%). The results of the analysis showed that there was a relationship between knowledge and Covid-19 prevention behavior (p = 0.02) and there was no relationship between attitude and Covid-19 prevention behavior (p = 0.06). Attitudes and behavior are very much determined by good knowledge, but good knowledge also needs to be supported by good beliefs so that it is necessary to synergize knowledge and beliefs to create appropriate attitudes and behaviors.